A regional extreme value analysis of ocean waves in a changing climate. (1st November 2017) - Vanem, Erik
Abstract: This paper applies regional frequency analysis on extreme significant wave heights in the North Atlantic ocean for historical and projected ocean wave climates. Regional frequency analysis is applied in order to perform spatial extreme value analysis over a large ocean area. One of the main advantages of regional frequency analysis is that one borrows strength for nearby locations by site pooling in order to get more accurate and robust estimates of extreme significant wave heights. Moreover, a set of homogeneous regions are identified as ocean regions with similar characteristics. In this way, the effect of climate change on the ocean wave climate can be studied, both with regards to changes in extreme quantiles at certain location and to overall spatial changes. The results from the regional frequency analysis are presented in this paper. The results are generally found to be reasonable, suggesting that regional frequency analysis can be useful in the analysis of extreme ocean waves. In particular, regional frequency analysis yields narrower uncertainty bounds and hence more robust estimation of extreme quantiles, corresponding to long return periods. Highlights: A regional frequency analysis for significant wave height is presented Spatial extreme value analysis for ocean waves Analysis of the effect of climate change on the ocean wave climate in North Atlantic The study demonstrates that regional frequency analysis is a useful tool in ocean engineering applications Results indicate that more robust estimates of high return values can be obtained by regionalization Results indicate that areas with extreme waves might be larger in future climate, even though the most extreme events decline